Moderate hypoxia mitigates the physiological effects of high temperature on the tropical blue crab Callinectes sapidus - Garcia-Rueda, Adriana L.; Mascaro, Maite; Rodriguez-Fuentes, Gabriela; Caamal-Monsreal, Claudia P.; Diaz, Fernando; Paschke, Kurt; Rosas, Carlos (Frontiers in Physiology, 2023)
Dissolved oxygen (DO) and water temperature vary in coastal environments. In tropical regions, the ability of aquatic ectotherms to cope with hypoxia and high-temperature interactive effects is fundamental for their survival. The mechanisms underlying both hypoxia and thermal tolerance are known to be interconnected, therefore, the idea of cross-tolerance between both environmental stressors has been put forward. We investigated the combined role of hypoxia and temperature changes on the physiological responses of blue crab Callinectes sapidus living in the southern Gulf of Mexico. We measured oxygen consumption, plasmatic biochemical indicators, total hemocyte count (THC), and antioxidant activity biomarkers in muscle and gill tissues of blue crab acclimated to moderate hypoxia or normoxia and exposed to a thermal fluctuation or a constant temperature, the former including a temperature beyond the optimum range. Animals recovered their routine metabolic rate (RMR) after experiencing thermal stress in normoxia, reflecting physiological plasticity to temperature changes. In hypoxia, the effect of increasing temperature was modulated as reflected in the RMR and plasmatic biochemical indicators concentration, and the THC did not suggest significant alterations in the health status. In both DO, the antioxidant defense system was active against oxidative (OX) damage to lipids and proteins. However, hypoxia was associated with an increase in the amelioration of OX damage. These results show that C. sapidus can modulate its thermal response in a stringent dependency with DO, supporting the idea of local acclimatization to tropical conditions, and providing insights into its potential as invasive species.